Analysis of phthalate esters in dairy products—a brief review. Issue 3 (3rd January 2017) - Fan, Yingying; Chen, He; Liu, Hejiang; Wang, Fulan; Ma, Sha; Latipa, Aierken; Wang, Shuai; Wang, Cheng
Abstract : This review provides a brief survey of pretreatment and instrumental detection methods for the analysis of PAEs in dairy products. Abstract : This review provides a brief survey of the physicochemical properties of phthalate esters (PAEs) and their harm to human health. The present analytical methods available for the determination of these compounds in dairy products are critically evaluated. The attention is primarily devoted to the methods for sample pretreatment, which are the main source of errors and are usually the most time-consuming step of the whole analysis. The characteristics of instrumental analysis methods, including gas chromatography, liquid chromatography, tandem mass spectrometry, capillary electrophoresis and immunoassay are discussed. Furthermore, the future development of analysis of PAEs is discussed.